2006
DOI: 10.1104/pp.105.070474
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hydrogen Peroxide-Producing and Hydrogen Peroxide-Consuming Peroxidases in the Leaf Apoplast of Cowpea in Manganese Tolerance

Abstract: The apoplast is considered the leaf compartment decisive for manganese (Mn) toxicity and tolerance in cowpea (Vigna unguiculata). Particularly apoplastic peroxidases (PODs) were proposed to be key enzymes in Mn toxicity-induced processes. The presented work focuses on the characterization of the role of hydrogen peroxide (H 2 O 2 )-producing (NADH peroxidase) and H 2 O 2 -consuming peroxidase (guaiacol POD) in the apoplastic washing fluid (AWF) of leaves for early stages of Mn toxicity and genotypic difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
86
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 64 publications
4
86
1
1
Order By: Relevance
“…The method was modified from that used to extract apoplastic wall fluid from leaves (Rathmell and Sequeira, 1974;Fecht-Christoffers et al, 2006). Arabidopsis roots (0.1-0.5 g fresh weight) were rinsed in DI water and then excised into 10 mM Na phosphate buffer (pH 6.0).…”
Section: Confocal Microscopymentioning
confidence: 99%
“…The method was modified from that used to extract apoplastic wall fluid from leaves (Rathmell and Sequeira, 1974;Fecht-Christoffers et al, 2006). Arabidopsis roots (0.1-0.5 g fresh weight) were rinsed in DI water and then excised into 10 mM Na phosphate buffer (pH 6.0).…”
Section: Confocal Microscopymentioning
confidence: 99%
“…This method has already been used not only for the determination of apoplastic metabolites but also for the extraction of apoplastic proteins (Boudart et al, 2005;Fecht-Christoffers et al, 2006). Pools of AWF from leaves from eight 6-week-old wild-type potato plants with reasonably low activity of UGPase, a soluble cytosolic enzyme with high activity and an almost identical molecular mass to that of apyrase, were prepared to analyze apyrase activity.…”
Section: Determination Of Apyrase Activity In Apoplastic Washing Fluimentioning
confidence: 99%
“…Therefore, it has been suggested that leaf chloroplasts might be primary targets of Mn toxicity, which could result in impairment of thylakoid structure and disruption of the electron transport chain in photosynthesis of plants (González et al, 1998;Lidon et al, 2004). In addition, Mn toxicity might also cause reactive oxygen species accumulation and brown spot formation in leaves, and may thereby inhibit plant growth more severely (Fecht-Christoffers et al, 2006). Although soil amelioration (e.g.…”
mentioning
confidence: 99%
“…In cowpea (Vigna unguiculata), compartmentalization of Mn in leaf apoplasts is considered as a primary response to Mn toxicity (Horst et al, 1999). Furthermore, accumulation of peroxidases in leaf apoplasts can modulate Mn oxidation, and thereby affect Mn tolerance in cowpea (Fecht-Christoffers et al, 2006). In addition, increased cell wall binding capacity of Mn and decreased hydroxyl radical accumulation in leaf apoplasts have been suggested to alleviate Mn toxicity with silicon (Si) application (Dragiši c Maksimovi c et al, 2012).…”
mentioning
confidence: 99%